A model predictive scheme to integral controller design for uncertain LTI systems with nonzero reference. (July 2020) - Ghaffari, Valiollah
Abstract: A model predictive method is developed to tune an integral controller for uncertain systems subjected to constrained input signals. For this purpose, a stabilizing integral controller is firstly designed for linear time-invariant (LTI) systems with polytopic uncertainty. The integral controller gains can be determined via a feasible solution of a linear matrix inequality (LMI). Then, a predictive control is incorporated into the integral controller synthesis through an optimization problem subjected to some LMI constraints. The suggested control is successfully applied to a typical uncertain system and an uncertain chemical reactor. The effectiveness of the proposed technique will be shown in comparison with other control methods. Highlights: A stabilizing controller is proposed to the integral control purpose for LTI systems with the polytopic uncertainty. A predictive control law would be presented to integral control synthesis in term of the optimization problem subjected to some LMI constraints. The suggested control law is successfully applied to some uncertain systems as well as the nonlinear chemical reactor. The effectiveness of the proposed controller would be demonstrated in comparison with the existing methods.